The world's most dangerous paper route [videorecording (DVD)] - Kroft, Steve; Hausle, Matthew; Freedman, Paul (Producer); Freedman, Paul (Producer); Barber, Steven C. (Vision Films, 2018)
"Witness the story of the unsung heroes who write and photograph for the Stars and Stripes, the U.S. military's oldest and most reliable newspaper, as well as those who deliver the newspaper to soldiers in Afghanistan along the world's most dangerous paper route. Narrated by former Stars and Stripes journalist Steve Kroft and featuring combat photographer Laura Rauch, Stars and Stripes Distribution Manager Robert Riceman, Senator Lindsey Graham, and Wounded Warrior Kyle Hockenberry."--Container